2018
DOI: 10.1186/s13059-018-1401-9
|View full text |Cite|
|
Sign up to set email alerts
|

Mutational signatures reveal the role of RAD52 in p53-independent p21-driven genomic instability

Abstract: BackgroundGenomic instability promotes evolution and heterogeneity of tumors. Unraveling its mechanistic basis is essential for the design of appropriate therapeutic strategies. In a previous study, we reported an unexpected oncogenic property of p21WAF1/Cip1, showing that its chronic expression in a p53-deficient environment causes genomic instability by deregulation of the replication licensing machinery.ResultsWe now demonstrate that p21WAF1/Cip1 can further fuel genomic instability by suppressing the repai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 82 publications
3
51
0
3
Order By: Relevance
“…In these cancer cells, DNA DSBs exist, but the DNA damage checkpoint pathway is compromised during cancer development, often by mutation/downregulation of checkpoint proteins [3,36,40]. Furthermore, inhibition of certain repair pathways would lead to a shift in repair mechanisms particularly to errorprone ones that facilitates genomic instability [41]. JMJD6 is upregulated in several types of cancer [42]; it is natural to speculate that JMJD6 overexpression-mediated inhibition of DNA repair may be one of the reasons for the increased genomic instability of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In these cancer cells, DNA DSBs exist, but the DNA damage checkpoint pathway is compromised during cancer development, often by mutation/downregulation of checkpoint proteins [3,36,40]. Furthermore, inhibition of certain repair pathways would lead to a shift in repair mechanisms particularly to errorprone ones that facilitates genomic instability [41]. JMJD6 is upregulated in several types of cancer [42]; it is natural to speculate that JMJD6 overexpression-mediated inhibition of DNA repair may be one of the reasons for the increased genomic instability of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best studied examples is E2F1, for which both KO and overexpressing mice have been generated and both develop tumors . Similarly, chronic expression of p21 was recently shown to cause genomic instability in addition to its long‐standing role as a tumor suppressor.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, RAD52 has been shown to perform roles either downstream or upstream DSBs formation [45,82,102]. Several works in the last years supported or reported a function for RAD52 in the repair of collapsed replication forks by BIR [45,47,59,109,110]. In yeast, the relevance of Rad52 for BIR have been vastly demonstrated over the years as well as it has been shown that Rad52 participates to both Rad51-dependent and independent BIR [42].…”
Section: Rad52 As a Partner Of Mus81mentioning
confidence: 99%
“…Since all this would happen in a situation in which RAD51 cannot be assembled to protect the fork-i.e., BRCA2-deficiency-it makes sense that a D-loop assembled by RAD51 is refractory to MUS81-dependent cleavage [102]. Worth noting, RAD52 is required to ensure replication fork progression under these situations although its activation greatly stimulates rearrangements being able to produce specific mutational signatures as found also in yeast cells [42,109,[115][116][117][118].…”
Section: Rad52 As a Partner Of Mus81mentioning
confidence: 99%
See 1 more Smart Citation